Preliminary evaluation of SaCoVLM video laryngeal mask-guided intubation in airway management for anesthetized children - Zhi, Juan; Deng, Xiao-Ming; Zhang, Yan-Ming; Wei, Ling-Xin; Wang, Qian-Yu; Yang, Dong (BMC anesthesiology, 2023)
To preliminary evaluate the application of novel SaCoVLM video laryngeal mask -guided intubation for anesthetized children. One hundred twenty-four children with microtia (ages 5-15 years,) who required general intubation anaesthesia, were enrolled in the study. After induction of general anesthesia,guided tracheal intubation under direct vision of the SaCoVLM was performed. Our primary outcome was first-pass success rate of guided tracheal tube placement. Secondary outcome included glottic visualization grades, the first-attempt success rate of LMA placement, the time for LMA placement and time to endotracheal intubation as well as the time for LMA removal after successful intubation, the fiberoptic grade of laryngeal view, the baseline and postinduction hemodynamic parameters were also recorded,and the incidence 24 h complications after operation. The first-pass success rate of guided tracheal tube placement was 91.1% (95%CI = 1.04-1.14), the status of glottic visualization was classified: grade 1 in 27cases, grade 2 in 36 cases, grade 3 in 41 cases and grade 4 in 20 cases. The first success rate of LMA placement was 92.7% (95%CI = 1.03-1.13), the time for LMA insertion was 15.7 (±9.1) s, intubation time was 30.9 (±17.6) s and withdrawl time was 24.9 (±9.3) s. The incidence of postoperative sore throat at 2 h was 29%, and 16.1% at 24 h, without dysphagia and hypoxia. The SaCoVLM video laryngeal mask-guided intubation is feasible in children, with a high success rate, could be a new promising device to guide intubation in airway management. This study was approved by the University's Institutional Review Board and written informed consent was obtained from all subjects participating in the trial. The trial was registered prior to patient enrollment at clinicaltrials.gov (ChiCTR2200061481, http://www.chictr.org.cn . Principal investigator: Juan Zhi; Date of registration: 26/06/2022.